Omnichannel Changing Hedonic Motivational Behavior? Creating Shopping Experience and Satisfaction Against Consumer Loyalty - Ardhiyansyah, Andri; Jaman, Ujang Badru (The Es Economics and Entrepreneurship, 2023)
Omnichannel is a new channel that can solve the current problems with consumers. The main objective of this study is to analyze whether there is an influence of omnichannel media on the nature of the hedonic motivation of consumers in making transactions. This study uses a quantitative approach to the survey method. Respondents in this study were 250 respondents spread throughout Indonesia using Smart-PLS 3. The results of this study where Consumer Experience affects Consumer Loyalty, where a good consumer experience will increase consumer loyalty. Consumer Satisfaction affects Consumer Loyalty; if consumers are satisfied, it will increase customer loyalty. Habit influences the Consumer Experience, where consumer habits in buying a product or service will enhance the consumer experience. Habit influences Consumer Satisfaction, where positive habits when purchasing a product or service will increase consumer satisfaction. Hedonic motivation affects the Consumer Experience, where integrated online and offline purchasing channels will make it easier for consumers to shop.